2015
DOI: 10.3748/wjg.v21.i13.3876
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylation is a common glycosylation type in pancreatic cancer stem cell-like phenotypes

Abstract: Fucosylation might be a biomarker of CSC-like cells in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…In our previous work, we identified increased levels of core and outer-arm fucosylation of a large number of serum and liver tissue proteins as being associated with HCC5678 and similar increases in fucosylation have been seen in other cancers91011121314151617.…”
mentioning
confidence: 61%
“…In our previous work, we identified increased levels of core and outer-arm fucosylation of a large number of serum and liver tissue proteins as being associated with HCC5678 and similar increases in fucosylation have been seen in other cancers91011121314151617.…”
mentioning
confidence: 61%
“…Fucosyltransferase expression in PC is associated with the increased expression of sialyl-Lewis a/x on the cancer cells [54], which act as the ligands for the selectins, present on the surface of endothelial cells, therefore, facilitating the interaction between cancer and endothelial cells during extravasation step of metastasis [54]. Further, fucosylation is also associated with the stem cell-like phenotype and the malignant transformation of intraductal papillary mucinous lesions [55]. …”
Section: Resultsmentioning
confidence: 99%
“…The identification of molecular biomarkers of drug sensitivity and drug resistance is critical for effective prognosis. A recent study on whole-genome characterization of chemotherapeutic-resistant ovarian cancer showed that 62 genes are simultaneously altered in cisplatin-, doxorubicin-, and paclitaxel-resistance phenotypes [14]. Acquired chemotherapy resistance is mainly associated with the inactivation of tumor suppressors, loss of BRCA1 promoter methylation, and overexpression of the drug efflux pump MDR1 [15].…”
Section: Introductionmentioning
confidence: 99%